2021
DOI: 10.1111/cod.13868
|View full text |Cite
|
Sign up to set email alerts
|

Patch test results in patients with suspected contact allergy to shoes: Retrospective IVDK data analysis 2009–2018

Abstract: Background: Allergic contact dermatitis caused by shoes is common and new relevant allergens have been identified.Objectives: To investigate the pattern of type IV sensitization in patients with suspected allergic contact dermatitis of the feet related to shoes as a presumed culprit trigger.Methods: Retrospective analysis of data of the Information Network of Departments of Dermatology (IVDK), 2009-2018.Results: Six hundred twenty-five patients with presumed shoe dermatitis were identified in a cohort of 119 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Colophonium is a well‐known cause of shoe allergy in glues and finishes or as tackifier. The frequency of sensitization to colophonium in patients with foot dermatitis was about twice as high as in the control group of patients with suspected contact sensitization to other allergen sources and comparable to earlier data according to a new retrospective study from the IVDK (Information Network of Departments of Dermatology) 27 . It should be noted that colophonium in shoes is often modified by esterification or Diels‐Alder reactions, whereby new strong sensitizers are formed that do not cross‐react with the haptens in unmodified colophonium 15,25,28,29 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Colophonium is a well‐known cause of shoe allergy in glues and finishes or as tackifier. The frequency of sensitization to colophonium in patients with foot dermatitis was about twice as high as in the control group of patients with suspected contact sensitization to other allergen sources and comparable to earlier data according to a new retrospective study from the IVDK (Information Network of Departments of Dermatology) 27 . It should be noted that colophonium in shoes is often modified by esterification or Diels‐Alder reactions, whereby new strong sensitizers are formed that do not cross‐react with the haptens in unmodified colophonium 15,25,28,29 …”
Section: Discussionsupporting
confidence: 87%
“…Departments of Dermatology). 27 It should be noted that colophonium in shoes is often modified by esterification or Diels-Alder reactions, whereby new strong sensitizers are formed that do not cross-react with the haptens in unmodified colophonium. 15,25,28,29 Because colophonium is a natural product, nontoxic and with very good adhesive properties, it finds usage when technical devices are fastened to the skin, such as insulin-infusion sets.…”
Section: Discussionmentioning
confidence: 99%
“…Three patients with relevant positive reactions to PPD were probably caused by dyes in black rubber and leather shoes. However, previous studies reported that shoe ACD from dyes was rare 5,23 . Chemical analysis of shoe materials should be done to confirm the clinical relevance of positive reactions as patients may have become sensitized to PPD through different exposures.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, patch testing with material samples would help to detect allergic reactions caused by unknown allergens or allergens not commercially available as test substance. There were new allergens that have been discovered by patch testing and analysis of material samples, such as isobornyl acrylate in glucose sensors and insulin pump 5,35 . Recently, Raison-Peyron et al 36 reported acetophenone azine as a new allergen that was responsible for severe contact dermatitis from shin pads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation